Modeling of relationships between physical and technical activities and match outcome in elite German soccer players - Konefal, M.; Chmura, P.; Kowalczuk, E.; Figueiredo, A. J.; Sarmento, H.; Rokita, A.; Chmura, J.; Andrzejewski, M. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The aim of this study was to determine what physical and technical activities of soccer players in different pitch positions affect significantly the match outcome of professional German soccer players; as well as to examine whether differences in physical and technical activities increase or reduce the probability of a match being won. METHODS: The study sample comprised 4393 individual match observations of 350 soccer players competing in the Bundesliga during the 2014/2015 domestic season. Analysis was confined to outfield players (other than goalkeepers) who completed entire matches, and was carried out using the Impire AG motion analysis system. The selection of physical and technical activities to be used in predictive models was achieved using the lasso method. RESULTS: The odds ratio revealed that an mean running speed in the second half that was greater by 0.1 km/h was associated with a 27.0% improvement in the odds of a match being won (OR=1.27; 95% CI: 1.17 to 1.38) (forwards), 15.7% (OR=1.16; 95% CI: 1.09 to 1.23) (wide midfielders), and 10.0% (OR=1.10; 95% CI: 1.04 to 1.17) (central midfielders). Furthermore, in the case of wide midfielders, a significant variable was the distance covered at >24 km/h, with an increase of 0.1 km associated with odds of winning the game improved by 31.7% (OR=1.32; 95% CI: 1.05 to 1.66). CONCLUSIONS: Match outcome is affected significantly where peak and mean running speeds in the second half of the match are greater, and where longer distances are covered at speeds in excess of 24 km/h.